Quantum coherent manipulation and readout of superconducting vortex states - Ameya Nambisan; Simon Günzler; Dennis Rieger; Nicolas Gosling; Simon Geisert; Victor Carpentier; Nicolas Zapata; Mitchell Field; Milorad V. Milošević; Carlos A. Diaz Lopez; Ciprian Padurariu; Björn Kubala; et al. (Nature, 2026)
Abstract A defining characteristic of superconductors is their tendency to expel magnetic fields, yet above a critical threshold, magnetic flux penetrates in discrete quanta carried by Abrikosov vortices 1 . The superconducting gap is completely suppressed at the vortex core, rendering them dissipative, semi-classical entities that impact applications from high-current-density wires to quantum devices. Material disorder can drive a crossover to vortices that preserve an energy gap at the core 2–4 , owing to intrinsic 5 or emergent granularity on the scale of the coherence length 2,6 . Although quantum vortex behaviour could emerge in this effective tunnel-junction regime 7 , and signatures have been observed in diverse systems 8–10 , coherent manipulation of vortex states has remained elusive. Here we present evidence that vortices trapped in granular superconducting films can behave as two-level systems, exhibiting microsecond-range quantum coherence and energy relaxation times that reach fractions of a millisecond. Using the tools of circuit quantum electrodynamics 11 , we perform coherent manipulation and quantum non-demolition readout of vortex states in granular aluminium microwave resonators, heralding future directions for quantum information processing, materials characterization and sensing.